Aggregate and distributional effects of a carbon tax - Christian Proebsting (National Bank of Belgium, 2024)
To identify the households most affected by a carbon tax I set up a multi-sector model with putty-clay technology. A 100-per-ton carbon tax cuts emissions by 25% after 5 years, but reduces output by 3% in the short run and 4% in the long run. Initially, the tax is progressive despite poorer households spending more on carbon-intensive goods, the prices of which rise. The complementarity of capital and energy causes a sharp decline in capital income, affecting top earners the most, and leads to job cuts in capital goods-producing industries that employ high-income earners. Over time the tax incidence flattens.
Keywords: D57; E62; Q52; 330; carbon tax; putty-clay; input-output linkages; income distribution